2016
DOI: 10.7314/apjcp.2016.17.s3.23
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CYP17, CYP19 and CYP1A1 Gene Polymorphisms in Iranian Women with Breast Cancer

Abstract: Breast cancer (BC) is the most common cancer and the second cause of mortality in women all around the world. It is caused by several factors including genetic determinants, so that both genetic susceptibility factors and environmental factors are involved in the etiology. Significance of genes functioning in steroid hormone synthesis and metabolism are well established in breast cancer susceptibility. In this study, 134 women with BC and 135 normal controls were analyzed for their genotypes for the polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…Our results are in line with some previous reports in different population like Indian,[30] Danish,[31] and American,[32] and different Iranian ethnic like Gilaki[33] and Fars. [34] Their finding revealed that there is no correlation between polymorphism M2 of CYP1A1 gene and breast cancer risk. Contrary to our results, some reports pointed out that there is a positive association between this polymorphism and risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with some previous reports in different population like Indian,[30] Danish,[31] and American,[32] and different Iranian ethnic like Gilaki[33] and Fars. [34] Their finding revealed that there is no correlation between polymorphism M2 of CYP1A1 gene and breast cancer risk. Contrary to our results, some reports pointed out that there is a positive association between this polymorphism and risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC), the second most common cause of cancer-associated mortality in women worldwide, is a heterogeneous disorder accompanied by systemic symptoms, including hot flushes, insomnia and mood changes, as well as local symptoms, including urogenital atrophy and vaginal dryness ( 1 , 2 ). According to a World Health Organization report published in 2015, the incidence of BC is 19.4 per 100,000 women in East Africa and 89.7 per 100,000 women in Western Europe ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 So far, the etiology of breast cancer has not been fully understood, but it was discovered that the development of breast cancer is associated with genetic and environmental factors as well as obesity, while hormone replacement therapy may also lead to breast cancer. 3 5 At present, traditional methods, such as sentinel lymph node biopsy, are typically used to determine the staging of breast cancer, but they are associated with high cost and technical complexity. 6 A new technology named contrast-enhanced ultrasound (CEUS) provides an earlier assessment of intrahepatic cholangiocarcinoma and hepatocellular carcinoma, as well as providing a prediction of neoadjuvant chemotherapy efficiency.…”
Section: Introductionmentioning
confidence: 99%